Phenotypic and genetic characterization of tomato mutants provides new insights into leaf development and its relationship to agronomic traits (2019)
Background: Tomato mutants altered in leaf morphology are usually identified in the greenhouse, which demands considerable time and space and can only be performed in adequate periods. For a faster but equally reliable scrutiny method we addressed the screening in vitro of 971 T-DNA lines. Leaf development was evaluated in vitro in seedlings and shoot-derived axenic plants. New mutants were characterized in the greenhouse to establish the relationship between in vitro and in vivo leaf morphology, and to shed light on possible links between leaf development and agronomic traits, a promising field in which much remains to be discovered. Results: Following the screening in vitro of tomato T-DNA lines, putative mutants altered in leaf morphology were evaluated in the greenhouse. The comparison of results in both conditions indicated a general phenotypic correspondence, showing that in vitro culture is a reliable system for finding mutants altered in leaf development. Apart from providing homogeneous conditions, the main advantage of screening in vitro lies in the enormous time and space saving. Studies on the association between phenotype and nptII gene expression showed co-segregation in two lines (P > 99%). The use of an enhancer trap also allowed identifying gain-of-function mutants through reporter expression analysis. These studies suggested that genes altered in three other mutants were T-DNA tagged. New mutants putatively altered in brassinosteroid synthesis or perception, mutations determining multiple pleiotropic effects, lines affected in organ curvature, and the first tomato mutant with helical growth were discovered. Results also revealed new possible links between leaf development and agronomic traits, such as axillary branching, flower abscission, fruit development and fruit cracking. Furthermore, we found that the gene tagged in mutant 2635-MM encodes a Sterol 3-beta-glucosyltransferase. Expression analysis suggested that abnormal leaf development might be due to the lack-off-function of this gene. Conclusion: In vitro culture is a quick, efficient and reliable tool for identifying tomato mutants altered in leaf morphology. The characterization of new mutants in vivo revealed new links between leaf development and some agronomic traits. Moreover, the possible implication of a gene encoding a Sterol 3-beta-glucosyltransferase in tomato leaf development is reported. © 2019 The Author(s).